Efficient resource utilization scheme for real-time IoT application for D2D communication: A distance and power-driven based approach. (15th March 2023) - Pandey, Krishna; Chandra, Saurabh; Arya, Rajeev
Abstract: Device-to-Device (D2D) communication provides real-time functioning support for IoT applications using fifth-generation (5G) technologies. In an In-band underlay D2D model, resource allocation is a key issue. To overcome this issue, a distance and power-driven model is proposed. A mathematical problem is formulated with the main objective is to maximizing the spectral efficiency of the network. This work utilizes the concept of distributed processing for achieving our goal. First of all, we proposed a d istance and p ower-driven based r esource a llocation m echanism (DPRAM) for the improvement in spectral efficiency by mitigating D2D and interference between the base station and D2D users. Then, the applicability of the proposed work has been checked by using the Sigmoidal and Logarithmic based utility functions for the delay tolerance device and real-time IoT application respectively. Simulation results show that the proposed work is capable of providing the best solution as compared to random allocation methods and pure ALOHA by 63.41% and 95.12% and 60% and 96% improvement in system capacity. Analysis of performance parameters such as sigmoidal and logarithmic utility function approves that our proposed approach may be suitable for delay tolerant and real-time applications, such as connected healthcare systems, smart farming, smart grid, etc.